A comparative study between the self-learning approach and the Reggio Emilia approach for early childhood education - Al-Enzi, Nahla Mousa; Al-Shubili, Alanood Mohammad; Al-Kharisy, Wafa Zaal; Al-Shanwani, Hania (Journal of Educational and Psychological Sciences, 2022)
The study aims to compare the self-learning approach and the Reggio Emilia approach. It reveals the similarities and differences between them, and the extent of benefits from the Reggio Emilia approach and its application in the Kingdom of Saudi Arabia. The study used the comparative method. The first stage of the study focused on identifying the self-learning approach and the Reggio Emilia approach by comparing the basic data. In the second stage an explanatory comparison of the similarities and differences between the two approaches was accurately made. Identifying the extent of the application of the Reggio Emilia approach in the Kingdom of Saudi Arabia was in the third stage. The results showed that there is agreement between the two approaches to focus on self-activities and to give the child the opportunity to choose the activities. On the other side, there is a clear difference between the two approaches in terms of origins, the nature of the activities provided to the child and the practices of teachers.